2008
DOI: 10.1175/2008jamc1941.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Large-Eddy Simulations of Scalar Transport in Atmospheric Boundary Layer Flow over Complex Terrain

Abstract: This paper presents high-resolution numerical simulations of the atmospheric flow and concentration fields accompanying scalar transport and diffusion from a point source in complex terrain. Scalar dispersion is affected not only by mean flow, but also by turbulent fluxes that affect scalar mixing, meaning that predictions of scalar transport require greater attention to the choice of numerical simulation parameters than is typically needed for mean wind field predictions. Large-eddy simulation is used in a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Until now, the coupled simulation of snow transport has been only implemented in regional climate models applied over large areas at horizontal resolution higher than 5 km (GallĂ©e et al, 2001;Lenaerts et al, 2012). However, previous works have shown that atmospheric models can be run at high resolution in complex terrain to simulate in coupled mode meteorological situations such as wildland fire (Mandel et al, 2011, resolution of 100 m) or scalar dispersion (Michioka and Chow, 2008, resolution of 25 m). These studies were successful at capturing the flow structures in complex terrain.…”
Section: Vionnet Et Al: the Coupled Snowpack/atmosphere Model Mesmentioning
confidence: 99%
“…Until now, the coupled simulation of snow transport has been only implemented in regional climate models applied over large areas at horizontal resolution higher than 5 km (GallĂ©e et al, 2001;Lenaerts et al, 2012). However, previous works have shown that atmospheric models can be run at high resolution in complex terrain to simulate in coupled mode meteorological situations such as wildland fire (Mandel et al, 2011, resolution of 100 m) or scalar dispersion (Michioka and Chow, 2008, resolution of 25 m). These studies were successful at capturing the flow structures in complex terrain.…”
Section: Vionnet Et Al: the Coupled Snowpack/atmosphere Model Mesmentioning
confidence: 99%
“…Chow et al (2006) and Weigel et al (2006Weigel et al ( , 2007 indicated that the complex thermal structure and dynamics of the atmospheric flow over the complex terrain present in the Swiss Alps may be reproduced in detail using ARPS with Moeng and Wyngaard's (1989) LES model turned on. Michioka and Chow (2008) also showed that ARPS performs well when configured to run in the LES mode. These authors coupled ARPS to a code that calculates the dispersion of passive pollutants and ran simulations in regions of highly complex terrain using one-way nested grids, where the highest resolution was 25 m in the horizontal directions.…”
Section: M S Paiva Et Al: Influence Of High-resolution Surface mentioning
confidence: 89%
“…ARPS was formulated to be run in either a RANS (ReynoldsAveraged Navier-Stokes) or a LES code that solves the threedimensional, compressible, nonhydrostatic, filtered NavierStokes equations. The relevant settings for our application requires the use of ARPS in the LES mode because the length scale is based on the grid spacing, as explained by , and the difference between RANS and LES in this case is in the definition of the length scale (Michioka and Chow, 2008). For the LES mode, the length scale employed in the eddy viscosity equation is based on the grid size, whereas the length scale for the RANS mode is based on a PBL (planetary boundary layer) depth or distance from the ground.…”
Section: M S Paiva Et Al: Influence Of High-resolution Surface mentioning
confidence: 99%
“…Vertical grid spacing of 2 m is utilized in both domains, up to a height of 84 m, above which vertical stretching is applied. Note that ARPS and ARPS-CANOPY have been applied in previous studies with horizontal and vertical grid spacing O (10 m) or smaller (e.g., Michioka and Chow, 2008;Dupont and Brunet, 2008). With this vertical grid structure, there are nine grid points at or below the canopy crown (canopy height is 18 m).…”
Section: Model Configuration and Parameterizationmentioning
confidence: 99%